Pengaruh Faktor Internal Dan Faktor Eksternal Terhadap Kinerja UMKM Di Kecamatan Pariaman Tengah Kota Pariaman - Zaki, Zaki; Dhani, Tahta Zefi (LPPM Universitas Dharma Andalas, 2025)
MSMEs have an important role in the economy. In order for business performance to continue to increase, influencing factors are needed, but the problems faced include still being weak, such as limited capital faced by business actors because banks make loans difficult, ineffective marketing and lack of knowledge about alternative financing and lack of support such as many government policies that are not pro-MSMEs, for example forced evictions, lack of training from related institutions. The study aims to determine the influence of internal and external factors on the Performance of MSMEs in Pariaman Tengah District, Pariaman City. This type of research is quantitative research. The population in this study were 3,352 MSME actors in Pariaman Tengah District, Pariaman City. The sample was selected using the Slovin formula, so that a sample of 97 respondents was obtained and the sampling technique used random sampling. The data collection technique used a questionnaire, while the data analysis method used multiple linear regression analysis tests. The results of the study showed that internal factors had an influence and were significant on MSME performance. This means that the stronger the influence of internal factors, the higher the MSME performance will tend to be. Conversely, the weaker the influence of internal factors, the lower the MSME performance will tend to be, external factors had an influence and were significant on MSME performance. This means that the stronger the influence of external factors, the higher the MSME performance will tend to be. Conversely, the weaker the influence of external factors, the lower the MSME performance will tend to be and internal and external factors simultaneously have a significant influence on MSME performance. This means that internal and external factors will affect MSME performance, if internal and external factors are good, MSME performance will be achieved.